2012
DOI: 10.1097/rlu.0b013e31823905e4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinicopathological Features and Expression of Molecular Markers With Prognosis After 131I Treatment of Differentiated Thyroid Carcinoma

Abstract: Male gender, and lymph node and distant metastases were found to be poor prognostic factors for patients with DTC. Higher expressions of ER, PR, HER-2, EphA-2, and NIS were associated with DTC, but were not correlated with the effectiveness of radioiodine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(28 reference statements)
1
11
0
2
Order By: Relevance
“…To date, many studies have evaluated HER2 expression in thyroid cancer with controversial results, largely due to inter-study differences in the size and setting of the examined series and, most of all, to the subjective assessment and lack of uniform methodology [14,15,16,17,18,19,20,21,22,23,24,25,26]. Indeed, studies reported in the literature in the past several decades markedly differ by the methodological approach used to assess HER2 status [14,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, many studies have evaluated HER2 expression in thyroid cancer with controversial results, largely due to inter-study differences in the size and setting of the examined series and, most of all, to the subjective assessment and lack of uniform methodology [14,15,16,17,18,19,20,21,22,23,24,25,26]. Indeed, studies reported in the literature in the past several decades markedly differ by the methodological approach used to assess HER2 status [14,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on HER2 have also been performed in thyroid cancer cells and tissues [14,15,16,17,18,19,20,21,22,23,24,25,26]. Interestingly, a wide variation in HER2 overexpression was reported in such studies, with positivity rates varying from 0% up to 70%, which may largely be attributed to inter-study technical and interpretive variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the well-differentiated forms, which are efficaciously managed by the treatment with surgery and radioiodine, an increased prevalence was reported also for the less differentiated carcinomas [1,3]. These tumors are unable to concentrate this radioisotope and do not respond to the standard treatment or develop radio resistance [4,5]. These unresponsive tumors are characterized by an altered phenotype, often including the reduction/loss of expression of sodium/iodide symporter (NIS) and thyroperoxidase (TPO), owing to the oncogenic activation of intracellular signal transduction pathways which control cell growth and differentiation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have proposed that combining CXCR1 inhibitors with HER-2 targeted therapies can play a role in better survival during the treatment of HER-2 over expressing breast cancers [22,23]. In thyroid cancer, previous studies showed conflicting results with HER-2 positivity rates varying from 0% to 70% [24][25][26]. Moreover, HER-2 expression was linked to estrogen receptors expression in thyroid tumours [13].…”
Section: Introductionmentioning
confidence: 86%